A, B and H Antigens In Brenner Tumors - Gaskin, Alvia; Davidsohn, Israel (Investigación Clínica, 2013)
We investigated the presenee of A, B and H blood groups in 43 Brenner tumors using the red eell adherenee test (RCA) with the purpose of seeing if the histogenesis of this tumor was related to the eoelomie Of germinal epithelium. The RCA test gives a positive reaetion when the tissue under study eontains the corresponding isoantigens and negative when they are absent. The only RCA positive struetures of the normal ovary are the coelomie epithelium, rete ovari and the mesonephric tubules. The results obtained in the Brenner tumors differed greatly: the epithelial nest gave a positive reaction in 23.2% of the cases and 39.5% were negative. The reaction was plus and minus (+-) in the same nest in 16.2% of the cases and in 20.9% was positive, negative and plus-minus in different nests of the same patient. We analized the different possible ofigins of the tumor according with the results of the test discarding the germinal or coelomic epithelium as the only one origin of Â¡t. We s~ggest that perhaps the multiple different responses of the test are more in aecord with the multiple origin that Greene gives to the tumor. Finally we analized the possibility of the tumor beeing rather aTeratoma coming from the germinal cell which differentiates into ectodermic structures giving the typical cellular nests of the Brenner tumor.